2012
DOI: 10.1258/ijsa.2009.009093
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome, mortality and their predictors among HIV-associated tuberculosis patients

Abstract: Summary The risk of death is significantly higher in HIV-infected patients with tuberculosis (TB). This study aims to evaluate the impact of demographic, clinical and laboratory characteristics on the treatment outcome and mortality of TB/HIV co-infected patients in a tertiary TB centre in Iran. In total, 111 patients were recruited from 2004 to 2007. Mycobacteriological studies and demographic, clinical, and laboratory data from all patients were analysed and predictors of unsuccessful outcomes as well as mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 17 publications
3
40
0
4
Order By: Relevance
“…Consistent with other studies, (Girardi et al, 2000;Tabarsi et al, 2012) find that using ART, with 2 or 3 drugs, has a protective effect (RR = 0.16 and 0.08 respectively) in relation to those who did not use any scheme or used monotherapy. Tabarsi et al (2012), showed protection through the use of art (P <0.001).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with other studies, (Girardi et al, 2000;Tabarsi et al, 2012) find that using ART, with 2 or 3 drugs, has a protective effect (RR = 0.16 and 0.08 respectively) in relation to those who did not use any scheme or used monotherapy. Tabarsi et al (2012), showed protection through the use of art (P <0.001).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with other studies, (Girardi et al, 2000;Tabarsi et al, 2012) find that using ART, with 2 or 3 drugs, has a protective effect (RR = 0.16 and 0.08 respectively) in relation to those who did not use any scheme or used monotherapy. Tabarsi et al (2012), showed protection through the use of art (P <0.001). Another cohort study conducted in Europe and North America 25, in cities with high incidence of Tb (20 cases per 100,000 population), shows that use of art is a protective factor (RR = 0.87), only when ART start with high CD4 count.…”
Section: Discussionsupporting
confidence: 88%
“…Gender was associated with progression to AIDS; the hazard of AIDS among women was significantly higher than among men, as previously reported by others [1,12,27]. Also the survival rate from AIDS to death was not any more significant as previously stated by others [4,13,22,27]. However, based on the study carried out by Mirzaei et al, the survival rate from AIDS to death was higher for women than in men [12].…”
Section: Discussionsupporting
confidence: 66%
“…Few studies of AIDS-free HIV-infected individuals in Iran have explored the potential impact of factors influencing the time for progression from HIV to AIDS and from AIDS to AIDS-related death. The only information comes from small, unrepresentative samples of the population [1,[10][11][12][13][14][15][16]. Therefore, this retrospective cohort study was designed and conducted in a high middle-income country to estimate the time from the HIV diagnosis to AIDS progression and the time from the AIDS initiation to the AIDS-related death and non-AIDSrelated death.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates of drug abuse in any form were reported in 31 studies (n=101,023 participants), and widely varied between 2.9% [54] and 93.7% [76]. The pooled prevalence of drug abuse was 33.6% (95% CI 28.2 to 39.3, 28,238 participants) (Figure 2).…”
Section: Overall Prevalence Of Drug Abuse In People Living With Hivmentioning
confidence: 99%